Femur shape analysis system using maximum-minimum centre skeletonization - Saw, Seow Hui (2024)

(untitled)
The medical field covers an expansive expertise to serve the needs of a particular human body. The most competitive and rewarding medical specialities is the orthopaedic surgery, which is mainly focused on improving? the lives of patients with mobility and disorder issues, such as arthritis, ligament sprains, femoral shaft fractures, etc. Femoral shaft fractures are common, and it is correlated with frequent morbidity and mortality. It is a major musculoskeletal disorder caused by tremendous force applied to the femur. One of the most common surgical treatments for fixation is intramedullary nailing (IM) procedure, which utilises a specially designed metal rod and screws to be implanted into the medullary canal. However, severe bowing of the femur and the increasing in the width of the medullary canal can result in a mismatch between the IM nail and the alignment of the femur. Such mismatch is a risk factor for anterior cortical perforation off the distal femur with subtrochanteric fractures and leg length discrepancy with fractures of the femoral shaft. Therefore, accurate three-dimensional (3D) preoperative planning is mandatory to facilitate the implant's design based on the obtained geometric data of the femur anatomy, especially for the bowed femur. This thesis presents an automatic orthopaedic analysis system, namely, 3D femur shape analysis system (3D-FSA) based on the extracted skeleton of each individual patient to provide an accurate 3D preoperative simulation. Inspired by the theory defined in 3D skeletonization, we implemented a straightforward approach, namely the maximum-minimum centre approach for the skeleton extraction from the 3D femur in 3D-FSA. The use of 3D skeletonization in statistical analyses of femur parameters and geometry is a relatively novel field. It has been shown that the skeleton of the 3D femur produced by 3D-FSA allows the orthopaedics to gain a better visualise anatomy, aid in analysis and planning for the complex surgery and implant measurements. This is mainly because the significant geometric and topological information of the 3D femur can be computed, by using the proposed maximum-minimum centre approach in 3D skeletonization module. There are four (4) phases in the development of 3D-FSA. The first (1st) phase involves the creation of the 3D femur data files in .obj format from a set of cross-sectional CT images. These text files are created and shared by the researchers from South Korea and they are I. J. Jung (University of Ulsan College of Medicine, Seoul), E. J. Choi (Department of Orthopaedics, Asan Medical Centre, Seoul), B. G. Lee (Division of Computer Engineering, Dongseo University, Busan) and J. W. Kim (Department of Orthopedic Surgery, University of Ulsan College of Medicine, Asam Medical Centre, Seoul). The 3D femur is then constructed in the second (2nd) phase. The medial axis (skeleton) is extracted in the third (3rd) phase and finally the results are analysed in the fourth phase (4th). 3D-FSA has been utilised by the mentioned researchers for conducting the morphometric evaluation and anatomical analyses among Korean population. They have verified and validated the reliability of our system. Extensions of the proposed approaches for 3D-FSA are discussed throughout this thesis.